Influence of plant growth regulators on fatty acid composition of Simarouba glauca DC. - Manasi, S. Patil; Ahilya, V. Waghmode; Narayankar, Chirag; Gaikwad, D. K. (Current Botany, 2021)
Simarouba glauca is a medicinally important oil yielding plant. It is a rainfed wasteland evergreen edible oil tree. Presowing soaked seeds of Simarouba glauca in various Plant Growth Regulators (PGRs) are analyzed to estimate their fatty acid composition. The fatty acids extraction was done using petroleum ether and fatty acid methyl esters (FAMEs) were analyzed by Gas Chromatography with Flame Ionization Detector (GC-FID). Due to the application of growth regulators stearic acid, lingoceric acid and linolenic acid enhances noticeably, while, total saturated fatty acids are augmented due to cysteine, Salicylic Acid (SA) and methionine treatments and monosaturated fatty acids elevated due to the application of 6-Benzylaminopurine (6-BA) whereas polyunsaturated fatty acids enhanced in response to Gibberellic Acid (GA) and Chlormequat chloride (CCC). The PGR induced changes in fatty acid composition predominantly in polyunsaturated fatty acids may certainly recover the oil quality of S. glauca seeds.